Sámi cultural heritage and tourism in Finland - Joy, Francis (Routledge, 2020)
What still carry great importance throughout Sápmi, the homeland areas of the indigenous Sámi people of Fennoscandia and the Kola Peninsula in Northwest Russia, are traditions and structures such as sacred places, rock carving images and rock paintings and drum symbolism and figures tied to the pre-Christian Sámi religion. A new paradigm is emerging within academic study that pays attention to the misuse of Sámi traditions on which a lucrative tourist industry exists. This industry relies on fake souvenirs that reflect Sámi traditions and cultural heritage, and some of the most sacred aspects of culture are reduced to artificial tourism art for the purposes of creating a commodity for sale and profit. The subject matter of appropriation of Sámi traditions in relation to drums and symbolism is fairly widespread in Finland because the Sámi have not had the resources or powers to protect their heritage. One of the main areas of appropriation of Sámi spiritual culture is the sacred painted drum used by the noaidi, the religious specialist in Sámi culture, often referred to as the shaman. Noaidi drums are extensively decorated with symbolism and figures portraying Sámi cosmology, which consists of sacred and holy places, sacrificial-offering sites, nonhuman spirits, animals, boats and human figures as well as Noaiddit who are in some cases depicted flying when engaged in out-of-body travel. As a consequence, Sámi shamanism, which is a central practice within the traditional Sámi religion, has been adapted in various ways to meet the needs of the tourist industry. Moreover, replica drums and other fake Sámi artifacts such as the traditional costume Gákti, Sámi dresses and designs that are passed down across families and identify who people are, have been manufactured and marketed within tourism enterprises for profit. Legislation from 2003, which is supposed to protect Sámi cultural heritage, is ambiguous as are guidelines within tourism, because there is no effective legal protection against copying and exploitation. ...